Pemanfaatan Limbah Ampas Tebu (Bagasse) sebagai Bahan Baku Pembuatan Karbon Aktif - Salsabila, Cut Nuraini; Thahirah, Afifah; Saskia, Saskia; Zaini, Halim (Jurnal Teknologi, 2024)
Activated carbon (activated charcoal) is a porous solid that contains 85-95% carbon, produced from materials containing carbon by heating at high temperatures. The aim of this research is to determine the effect of variations in carbonization temperature on the final results of making activated carbon and to determine the effect of variations in the size of activated carbon particles on the final results of making activated carbon. The manufacture of activated carbon is carried out in 2 stages, namely the carbonization process using the pyrolysis method and activation using the chemical HCl 0.1 N. Activated carbon from sugar cane bagasse is made by varying the carbonization temperature of 250°C, 350°C, and 400°C with particle sizes 80 mesh, 100 mesh, and 120 mesh. The best activated carbon from the results of this research was found in activated carbon with a carbonization temperature of 250°C with a particle size of 120 mesh. This activated carbon has a yield value of 40%, water content of 1.89%, ash content of 5.72%, and iodine absorption capacity of 1,1447.0 mg/g.